Sustainable Finance: Bridging the Gap in Asia and the Pacific - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2025)
This report is part of ESCAP Financing for Development Series. The report examines the trends, challenges, and opportunities that policymakers, regulators, and private finance (banks, issuers, and investors) in Asia and the Pacific face in mobilizing public and private financing for key Sustainable Development Goals (SDGs), particularly around climate action. Its aims to spur a more robust and informed debate amongst key stakeholders within member States, to establish consensus on critical measures to move the region towards a net zero path and to bring greater clarity regarding the benefits and consequences of selected policy and financing choices in the short and the long- term. The report proposes eight Principles for Action in Sustainable Finance for further deliberation and dialogue among ESCAP member States: (1) the establishment of new partnerships for financing climate action, including policymakers, regulators and private finance; (2) effective NDC financing strategies helmed by government authorities with sufficient mandate and authority to implement them; (3) Redoubling of efforts to build capacity in climate, carbon and financial skills of policymakers, regulators and private finance; (4) Regulation to drive forthcoming change in financing decisions; (5) Policymakers need to send clear signals to investors who make investment decisions; (6) strengthen project preparation through engaging private finance and project developers in the pre-investment phase; (7) local investors in Asia and the Pacific need to adopt net zero pledges in line with NDCs; and (8) regional cooperation on taxonomy alignment, convergence, project preparation, cross-border capital investment and data comparability.